Penurunan konsumsi bahan bakar pada mesin bensin 4 langkah 1 silinder dengan menggunakan medan magnet elektomagnetik - Mara, I.M.; Alit, I.B.; Nuarsa, I.M. (Universitas Mataram, 2021)
The quality of gasoline fuel is very important; therefore scientists are trying hard to improve the quality of this fuel. One of them is treating the fuel before it enters the combustion chamber or before experiencing the combustion process. The use of permanent magnets can reduce fuel consumption, and reduce exhaust emissions. This study aims to investigate the reduction of fuel consumption of a single-cylinder four-stroke gasoline engine by using electromagnetic field. Diameter and length of the copper wire used are 0.7 mm and 80 meters. The effect of the magnetic field on the engine performance was observed at various engine speed, such as 1500, 3000, 4500 and 6000 rpm. The results showed that the electromagnetic of solenoid winding reduced the specific fuel consumption. The percentage of reduction in the specific fuel consumption is 18.93%.